Konsep Dynamic Capital Structure Adjustment Model (DCSA) sebagai Penentu Pengambilan Keputusan Struktur Modal pada UMKM - Isnaeni Rokhayati (JBIMA (Jurnal Bisnis dan Manajemen), 2018)
This research seeks to test the dynamic capital structure model in Micro Small and Medium Enterprises (MSMEs) in Banyumas Regency. The data used are panel data from MSMEs in Banyumas Regency from 2015 to 2017. This research uses dynamic model, which is different from the static model because this dynamic model incorporates adjustment rate parameter on leverage. Adjustment speed to targeted leverage is characterized as an activity to balance leverage at the targeted level. In a dynamic perspective, the leverage observed at a time may not be the same as the targeted leverage. Leverage targeted by these MSMEs will be determined and estimated. This study uses prediction of debt ratio as optimal leverage or targeted leverage. Targeted leverage changes from time to time due to changes in internal and external factors of MSMEs. This targeted leverage depends on the characteristics of MSMEs and macroeconomic conditions. Company's financial performance can be known from the optimal use of the capital structure. Capital structure theory such as pecking order theory and trade-off theory is widely used to determine funding policy in its capital structure. The development of trade-off theory and pecking order theory is to solve the problem of the capital structure into a model of the dynamic capital structure. The purpose of this paper is to explain the existence of adjustment model to the time of continuous leverage usage in capital structure at MSMEs which is development of dynamical capital structure theory that is dynamic capital structure adjustment model (DCSA) a new concept to solve funding problem at MSMEs, and using characteristic variable company in the form of profitability, assets structure, size, growth and liquidity as determinant factor of optimal capital structure at MSMEs. Previous research has been done in large companies, and still little done to MSMEs, so this research will test the structure of capital structure at MSMEs. The descriptive statistic research will be conducted by regression analysis. The sampling method used purposive sampling technique where the object of research is MSME which has financial report in last three years, data in the form of primary data from financial report of MSMEs. With the new concept of dynamic capital structure adjustment model (DCSA) is expected to determine the optimal capital structure with the level of adjustment (speed of adjustment) on leverage targeted at MSMEs.